2013
DOI: 10.1109/tpel.2012.2220157
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-Based Stability and Transient-Performance Assessment Applying Maximum Peak Criteria

Abstract: Abstract-The impedance-based stability-assessment method has turned out to be a very effective tool and its usage is rapidly growing in different applications ranging from the conventional interconnected dc/dc systems to the grid-connected renewable energy systems. The results are sometime given as a certain forbidden region in the complex plane out of which the impedance ratioknown as minor-loop gain-shall stay for ensuring robust stability. This letter discusses the circle-like forbidden region occupying min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 26 publications
0
84
0
Order By: Relevance
“…In each case, the energy variation is related to the maximum reactive energy in the magnet, E m = 1/2L m I 2 ref . It can be observed that the maximum energy variation of the storage element in strategy EB corresponds to the maximum reactive energy in the magnet, which is a consequence of the energy balance shown in (2). In strategy GCBP, the energy variation is greater than in the case of strategy EB, since during magnet pulse generation the capacitor C st must supply both the reactive energy and the active energy.…”
Section: Comparative Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…In each case, the energy variation is related to the maximum reactive energy in the magnet, E m = 1/2L m I 2 ref . It can be observed that the maximum energy variation of the storage element in strategy EB corresponds to the maximum reactive energy in the magnet, which is a consequence of the energy balance shown in (2). In strategy GCBP, the energy variation is greater than in the case of strategy EB, since during magnet pulse generation the capacitor C st must supply both the reactive energy and the active energy.…”
Section: Comparative Analysismentioning
confidence: 93%
“…Additionally, a proper design of the input filter avoids that the H-bridge input current affects the voltage v dc and, hence, avoids stability issues [2,3,4]. Then, the simplified circuit of the Fig.…”
Section: Converter Model Descriptionmentioning
confidence: 99%
“…The analysis methods are developed further in many publications (e.g., [28,42,[117][118][119][120][121][122][123][124][125][126][127]). The further developments are mainly concentrated on enlarging of the allowed area in complex plane, where the impedance ratio is allowed to lie without causing instability [117,118,122], on making the special parameters governing the interactions in the converters to be explicitly solvable [119,122], and on extending the methods into the grid-connected three-phase converters as well [123][124][125][126][127].…”
Section: Grid-forming-mode Operationmentioning
confidence: 99%
“…(1), (2), (5), (6) we get two equations each for L1 and L2. Tsh and Tnon are the shoot through and non-shoot through times respectively, their sum being the total switching time [15]. Calculating inductor voltage for the whole switching instant, the capacitor voltages can be rearranged and determined.…”
Section: Review Of a Quasi Z-source Invertermentioning
confidence: 99%